Challenges in Tracking of Fluorochrome-Labelled Nanoparticles in Mice via Whole Body NIRF Imaging - Gaffron, Florian (Nanomaterials (Basel), 2020)
Fluorochrome-labelled iron oxide magnetic nanoparticles (MNP) have been of great help in elucidating biological processes. Here, we used dually-fluorochrome-labelled MNP and studied to what extent fluorescence detection could reflect their fate in living animals. One day after application in mice (200 µmol Fe/kg body weight), the fluorescence of the dye attached to the core (DY-730) was very prominent and in agreement with the increase of iron in the liver and spleen of mice, but inconspicuous at time points thereafter. We attribute this fluorescence behavior to early degradation processes of the MNP´s core in the cellular lysosomal compartment. In contrast, the fluorescence of the dye DY-555 stuck to the PEG coating was not detectable in vivo. In summary, labelling of MNP with dyes at their metallic core could be of help when detecting first incidences of MNP biodegradation in vivo, as opposed to dyes attached to the MNP coating.